PADI open water diver video ([S.l.] : PADI, 2005)
Learn more about scuba diving from the experts at PADI.
Disc 1: Sections 1-2. Disc 2: Sections 3-5.
DVD, regions 1-6; NTSC standard screen (4:3); Dolby 2.0 stereo.
English , Spanish, Swedish, Norwegian, Finnish, Danish (Disc 1 and 2).
Keywords: Scuba diving -- Study and teaching; Scuba diving; Video recordings for hard of hearing people